The influence of glass on the airborne sound insulation of windows - ZAJAC, A. (Archives of Acoustics, 2000)
From the viewpoint of acoustics, the window is a rather complicated structure and its sound insulation depends upon numerous designing modifications, some of which are of decisive importance. They include blazing, infiltration, the window frame with fixed glass and the window structure itself.